G564(P) Neonatal jaundice assesment form – a tool to improve management of babies with jaundice. (27th April 2016) - Osmulikevici, O; Garbash, M; Hooper, K; Miller, M
Abstract : Context: The project took place in a District Hospital with a grade 2 Maternity Unit with approximately 3000 deliveries/year. The population targeted were babies with jaundice, in the postnatal ward or in the community. The purpose of the project was to develop a tool for midwives and junior doctors to asses jaundice and be able to design a management plan sensible and safe. The tool was meant to create a common 'language', helping communication, and to create a Trust approved framework for jaundice assesment. All relevant information would be recorded in one place, as opposed to being scattered in mother's and babies' notes, and easier available to those interpreting results. After consultations with the Paediatric team and the Midwifery Team, we developed a form to be used in the assesment of jaundice in the community and in the postnatal ward. Problem: During my first month of training in the Unit, I noticed that a significant number of babies were tested frequently for bilirubin levels, although they did not have specific risk factors for jaundice. Some babies did not need treatment for jaundice, however they underwent a significant number of blood tests. There was an increase in 'medicalising' babies otherwise normal with increase in anxiety levels for parents, painful procedures carrying a risk of infection for babies and increased work load for staff. Assessment of problem and analysis of its causes: After discussing with my Paediatric colleagues and the Midwives it was showed that this practice was due to applying rigorously and possibly out of context of a chart from the NICE guidelines. I felt that a better understanding of the causes for significant jaundice in babies and creating a tool to help quantify the risk will improve care. Intervention: We developed a chart to use when assessing babies with jaundice. The chart contains demographic information, for mother and baby, and questions targeting specific risk factors for jaundice as per NICE guidelines. The bilirubin levels and type of treatment are recorded. The advice given, the management and follow up plans are recorded, therefore it becomes easier to follow the accountability links and the thought process of the people involved in the management of the baby. Study design: To develop the chart, we organised 'brain- storming' sessions, both with the Paediatric team and the Midwifery team to extract the most important aspects of care in the management of babies with jaundice. I looked at existing Trust guidelines and NICE guidelines, to include them in our assement. Strategy for change: I presented the chart to both teams as part of our teaching sessions. A proposal was submitted to the Trust Committee to include the chart in the guidelines. Measurement of improvement: An audit will be performed to measure the outcome. On short term, the understanding of staff improved and less testing was observed in the months following. Effects of changes: The babies are submitted to less testing, which improves the outcomes both for babies and their parents. Lessons learnt: I understood better the level of involvement of each staff member in the care of babies with jaundice. The project underlined the pitfalls of guidelines and the fact that a good understanding and approach to a guideline is just as important as the guideline itself. Message for others: 'The way to apply a guideline is as important as the guideline itself'.